Characterization of Refractory Alloys Produced by Laser Additive Manufacturing. (24th November 2022) - Kustas, Andrew B.; Pegues, Jonathan; Melia, Michael A.; Whetten, Shaun R.; Jones, Morgan; Argibay, Nicolas
Abstract : Refractory alloys often possess superior thermomechanical properties compared to conventional materials, such as steels, Ni-based superalloys, and Ti alloys, especially in high-temperature environments. While these materials promise to revolutionize numerous industries, significant hurdles remain for insertion into applications due to an incomplete understanding of structure-property relationships and conventional processing challenges. We explore laser-based additive manufacturing (AM) to construct refractory alloys consisting of combinations of Mo, Nb, Ta, and Ti with systematically increasing compositional complexity. Microstructure, composition, and hardness of the AM-processed alloys were characterized. Results are discussed in the context of pairing additive manufacturing with refractory metals to enable next-generation alloys.